Efisiensi dan Kecernaan Ransum Domba yang Diberi Silase Ransum Komplit Eceng Gondok Ditambahkan Starter Lactobacillus plantarum - Eni Ekawati; Anis Muktiani; Sunarso Sunarso (Jurnal Agripet, 2014)
(Efficiency and digestibility feed of sheep given silage complete feed water hyacinth added starter lactobacillus plantarum)ABSTRACT. This study aims to determine the effect of a complete ration of silage made from water hyacinth on feed efficiency and digestibility. This study uses fifteen rams (12 months old with an average body weight of 19 3.98 kg). The experimental was designed completely random. The sheeps were randomly divided into 3 treatments, and 4 replications. The sheeps wereted concentrate and fresh elephant grass (T0), silage-based rations complete without the addition of starter hyacinth L. plantarum (T1), and a complete ration silage made from water hyacinth by the addition of L. plantarum starter (T2). Feed structured treatment isoenergi and isoprotein (PK 13% and 65% TDN). Feed treatment was given for 12 weeks with a 2-week adaptation period. The results showed that feed intake, ADG, feed conversion, and feed efficiency were not significantly different (P 0.05), but it can improve feed digestibility (P 0.05) between treatments. Feed intake data, digestibility, ADG, feed conversion and feed efficiency at T0, T1 and T2 as follows: 678.27, 811.43, 701.21 g / day; 70.51, 71.74, 69.82%; 94.09, 106.34, 97.28 g / day; 7.22, 7.66, and 7.18; 14.09, 13.23 and 14.02% use a complete ration silage with L. plantarum starter better than the control treatment in the form of concentrates with elephant grass but not better than silage without a starter.